2020
DOI: 10.1371/journal.pone.0228846
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy and safety of fecal microbiota transplantation and probiotic VSL#3 for active ulcerative colitis: A systematic review and meta-analysis

Abstract: Background Fecal microbiota transplantation is an effective treatment for many gastrointestinal diseases, such as Clostridium difficile infection and inflammatory bowel disease, especially ulcerative colitis. Changes in colonic microflora may play an important role in the pathogenesis of ulcerative colitis, and improvements in the intestinal microflora may relieve the disease. Fecal bacterial transplants and oral probiotics are becoming important ways to relieve active ulcerative colitis. Purpose This systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…In addition, no statistical difference was observed between FMT and the probiotics in terms of clinical efficacy. Despite these promising results, the authors point to many unresolved issues regarding the clinical application of these alternatives, suggesting that more randomized controlled trials are needed [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no statistical difference was observed between FMT and the probiotics in terms of clinical efficacy. Despite these promising results, the authors point to many unresolved issues regarding the clinical application of these alternatives, suggesting that more randomized controlled trials are needed [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The VSL#3 treatment determines anti-inflammatory effects in experimental colitis, as evidenced by reduced disease activity index (DAI) score, histological activity index (HAI) score and myeloperoxidase (MPO) activity [120]. Furthermore, in different randomized, double-blind, placebo-controlled trials the use of VSL#3 in UC patients showed significant effects in terms of clinical remission and clinical response during active UC with no side-effects [81,121]. However, the efficacy of probiotics in IBD remains uncertain, since different meta-analyses showed that there were no significant differences of remission, relapse, and complication rate between probiotics and placebo group, thus, more evidences from randomized clinical trials (RCTs) are required [122,123].…”
Section: Probiotics and Lbpsmentioning
confidence: 99%
“…Treatments for IBD include several classes of drug therapy, i.e., immunosuppressants, corticosteroids, aminosalicylates, and, more recently, monoclonal antibodies, in addition to palliative treatments like antibiotics, analgesics, anticholinergics, and antidiarrheal agents [3,9,17]. Holistic treatments and therapies emphasizing the importance of diet as well as intentional microbial shifts through the use of probiotics and heterologous and autologous fecal microbiota transplantation (FMT) have also gained momentum in recent years [18][19][20], although currently FMT is only FDA-approved for use in qualified recurrent Clostridium difficile associated infection in patients. Proper treatment and diagnosis of IBD are important as they have the potential to significantly improve patients' daily lives as IBD can become a crippling disease.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%